2011
DOI: 10.1016/j.ajhg.2011.01.017
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-wide Association Study Identifies Genetic Variation in Neurocan as a Susceptibility Factor for Bipolar Disorder

Abstract: We conducted a genome-wide association study (GWAS) and a follow-up study of bipolar disorder (BD), a common neuropsychiatric disorder. In the GWAS, we investigated 499,494 autosomal and 12,484 X-chromosomal SNPs in 682 patients with BD and in 1300 controls. In the first follow-up step, we tested the most significant 48 SNPs in 1729 patients with BD and in 2313 controls. Eight SNPs showed nominally significant association with BD and were introduced to a meta-analysis of the GWAS and the first follow-up sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
187
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 260 publications
(195 citation statements)
references
References 40 publications
7
187
1
Order By: Relevance
“…NCAN (neurocan) on chromosome 19p13.11 was identified as a genome-wide significant risk locus for BD in the first MooDS study 8 . In our present analysis, a SNP in strong LD with the original SNP rs1064395 (r 2 ¼ 0.96) showed a sub-genome-wide significant result (rs2011503-C, P GC ¼ 8.79 Â 10 À 8 ; OR ¼ 0.87).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…NCAN (neurocan) on chromosome 19p13.11 was identified as a genome-wide significant risk locus for BD in the first MooDS study 8 . In our present analysis, a SNP in strong LD with the original SNP rs1064395 (r 2 ¼ 0.96) showed a sub-genome-wide significant result (rs2011503-C, P GC ¼ 8.79 Â 10 À 8 ; OR ¼ 0.87).…”
Section: Resultsmentioning
confidence: 99%
“…Over the last 5 years, the MooDS consortium produced two waves of genome-wide data for BD. The first wave of data (Germany I) were generated for the GWAS by Cichon et al 8 and are now part of the PGC-BD GWAS data 7 . The second wave of data were generated for the present GWAS and are described below.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Large scale collaborative genome‐wide association studies (GWAS) have identified a number of risk loci significantly associated with bipolar disorder (BP), including ODZ4 [Sklar et al, 2011; Muhleisen et al, 2014], CACNA1C [Ferreira et al, 2008; Sklar et al, 2008], ANK3 [Ferreira et al, 2008; Schulze et al, 2009; Muhleisen et al, 2014], NCAN [Cichon et al, 2011], C15ORF53 [Ferreira et al, 2008], and DGKH [Baum et al, 2008a,2008b]. Individually, each of those genes/loci contributes only a small fraction toward overall disease risk, typically <1% of the phenotypic variance [Ferreira et al, 2008].…”
Section: Introductionmentioning
confidence: 99%